Tribological behaviour of UHMWPE composites lubricated by polyvinylpyrrolidone‐modified water. (29th September 2021) - Dhakal, Nayan; Shi, Yijun; Emami, Nazanin
Abstract: Tribological characteristics of ultra‐high molecular weight polyethylene (UHMWPE) composites with 10% short carbon fibres (SCF) lubricated in water with polyvinylpyrrolidone (PVP) as a modifier were investigated. The aqueous solutions with varying concentrations of PVP were prepared, and their viscosity‐enhancing action, friction‐reducing properties and anti‐wear performances were studied under different loading conditions equivalent to 10 and 20 MPa of contact pressures at a constant sliding speed of 20 mm/s. The results showed that PVP is an excellent viscosity modifier for water. PVP‐modified water exhibited excellent performance compared to distilled water, reducing the wear and friction coefficient of neat UHMWPE up to 25%. The anti‐wear properties of UHMWPE‐SCF composite were also improved with PVP modified water lubrication, yielding a maximum reduction of wear up to 45%. PVP seems to be a promising additive of modifying the lubricating properties of distilled water for water‐based lubrication.